Etos Kerja dalam Hindu dan Relevansinya dengan Kompetensi Abad 21 - Suartini, Ni Kadek; Surpi, Ni Kadek (Satya Widya: Jurnal Studi Agama, 2022)
Abstract The work ethic is a very important basic value inculcated in the Vedas. This work ethic will lead mankind to prosperity and a quality life. The work ethic in the Vedas is a basic skill that can be developed according to the needs of the times. The 21st century, which is marked by the development of science and technology, has changed many things in human life, including the types and ways of working. However, the work ethic taught in the Vedas such as diligent, persistent, creative, strong and shrewd in managing finances is the basic capital in life. Meanwhile in the 21st century, various skills such as communication, creativity and innovation, collaboration and critical thinking skills are needed to actually find their connection with the spirit and values that have been taught since ancient times. Humans and Hindus should find enthusiasm with the basic capital of the work ethic that has been taught since ancient times.